– Kościół – człowiek – świat. Odnowa soborowa w ujęciu Karola Wojtyły - DOBRZYŃSKI, Andrzej (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2012)
The article focuses on the problem of the process of the renewal of Christian life begun with the Second Vatican Council. The presentation of this central theme has been accomplished by means of an analysis of pastoral letters and homilies authored by Karol Wojtyła, Archbishop of Cracow, dating mainly from the time of the Council. According to Wojtyła, the renewal of Christian life fostered by the Second Vatican Council involves the effort to render the spiritual and theological foundation of the Church more expressly. Thus the event of the Council itself is perceived by him as the work of the Holy Spirit, who leads the faithful towards the truth revealed by Christ, permeates the mission of the Church in the world, and unites people. The pastoral and doctrinal character of the Vaticanum Secundum, as interpreted by Wojtyła, was an indication of the Church’s concern for man and for shaping the lives of the faithful according to the truth of faith. In his opinion, the task of the post-Conciliar renewal consists, above all, in «purifying» the main channels through which the Christian truth and grace influence human life, both in its individual and social dimensions, so that a growing recognition of the gift of Redemption in Christ will be accompanied by a growing responsibility for the salvation of the world. Translated by Dorota Chabrajska